Education for Relationships: The Reflective Journal as a Formative Method for Secondary School Teachers - Madrussan, Elena (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2023)
The article briefly describes the structure and development of the two training meetings in the pedagogical field related to the first edition of TEdu. The topic of the course - interpersonality - recalls the importance of the educational and formative relationship at school, with particular attention to the dynamics subsequent to the pandemic crisis. Starting from reciprocity as a key category of the relationship, the article illustrates the reasons for choosing the writing of the logbook as a tool for teachers, analyses the device in its main components and proposes a synthetic reading of the outcomes of its use.